The Effect of the Merdeka Mengajar Platform on Teachers' Creativity and Teaching Innovation at SMK Negeri 9 Kabupaten Jeneponto - Arbi Arbi; Nawir Rahman; Hartini Hartini (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyse 1.) the implementation of the Merdeka Mengajar Platform (PMM) at SMK Negeri 9 in Jeneponto Regency. 2). The influence of the Merdeka Mengajar Platform (PMM) on teacher creativity at SMK Negeri 9 in Jeneponto Regency. 3). To analyse the impact of the Merdeka Mengajar (PMM) platform on teachers' teaching innovation at SMK Negeri 9 Jeneponto District. This research uses a quantitative research approach. The study was conducted on 55 teachers at SMKN 9 Jeneponto. The sampling technique used in this research is total sampling. This means that the entire population was included as the sample in the study, resulting in a sample size of 55 teachers. Data collection techniques used questionnaires, and data analysis techniques used simple regression analysis, t-test analysis, and F-test analysis using SPSS 26. Research Findings 1). The Merdeka Mengajar Platform at SMK Negeri 9 Jeneponto is assessed as having been implemented effectively, and the results of measuring the Merdeka Mengajar Platform indicators at SMK Negeri 9 Jeneponto indicate that the Merdeka Mengajar Platform has positively impacted teachers' creativity and innovation in teaching at SMKN 9 Jeneponto. 2). There is a positive and significant effect of the Merdeka Mengajar Platform on teachers' teaching creativity at SMK Negeri 9 Jeneponto, and 3). There is a positive and significant effect of the Merdeka Mengajar Platform on teachers' teaching innovation (Y2) at SMK Negeri 9 Jeneponto